The automorphism groups and derivation algebras of two-dimensional algebras - Houida, Ahmed; Bekbaev, Ural; Rakhimov, Isamiddin (Journal of Generalized Lie Theory and Applications, 2018)
The automorphisms groups and derivation algebras of all two-dimensional algebras over algebraically closed fields are described